Evaluation of yield stability in sunflower hybrids by AMMI analysis: Evaluation of yield stability in sunflower hybrids by AMMI analysis - R SASIKALA; V SANTHIYA; T SELVAKUMAR; L RAJENDRAN; D UMADEVI; T KALAIMAGAL (Journal of Oilseeds Research, 2023)
A total of 15 sunflower hybrids and 3 checks with three season experimental data for seed yield have been utilized for stability analysis in sunflower. Study revealed that presence of significant difference among genotypes/seasons and also due to interaction of significance for PCA1, PCA2 and PCA3. Among these, PCA1 alone recorded 92.30 percent of total sum of squares. High yielding sunflower hybrids viz., CSFH 19004, CSFH 19087 and CSFH 19086 had PCA1 score close to zero indicating that these genotypes were less influenced by environments. Hence, the above said hybrids were stable and had general adaptability for both Kharif and Rabi seasons.